Getting There Women's Journeys to and Through Educational Attainment - Pemberton, Cynthia Lee A.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
This book chronicles the lived experience/educational journeys of women who found themselves moving forward together pursuing doctoral degrees in Educational Leadership. Grounded in the realities of women$1 (Bs lives these inspirational first-person narratives have the potential to raise awareness regarding women$1 (Bs socialization, expectations, and the role interpersonal and community connections play in the lived female experience. This book provides a potential resource for those considering how relationships and support groups impact life$1 (Bs journey, and their importance in overcoming barriers to educational attainment and success. In her book Flux, Peggy Orenstein encourages women to share their experiences, and (3z(Btalk across lines of age and circumstance(3y (B(p. 292). This book does that, bringing into focus the complicated and convoluted, knotty, thorny, messy realities of women$1 (Bs lives. Seeing clearly the forest and the trees, the grass, the shrubs, and dirt$1 (Bthe fully fleshed-out realities, we, as educators, can more fully and accurately see and appreciate the conflicting, competing chaos that characterizes and often monopolizes women$1 (Bs lives; and from there establish a foundation of understanding from which to begin retooling higher education to better meet the life and learning needs of all our students. (3z(BIn the end$1! =(3y (BOrenstein says, (3z$1! =(Bthere is no single path to a textured, satisfying life-nor should there be(3y (B(p. 293); and indeed, as this book reveals there is not. Despite geographical and generational differences, these women$1 (Bs independent and intersecting lives created, and even today supports and sustains their ongoing connection, empowerment and achievements, and as such not only leaves a legacy for others, but a blueprint of and for hope.s
Keywords: Education; Education; Education (general).